SEVERAL PARADIGMS IN INTERPRETATING PLATO’S PHILOSOPHY (Annual of the Faculty of Philosophy in Skopje, 2011)
There is no other work in the history of philosophy that was as equivocally interpreted as the work of Plato. Considering the interpretative history of Plato 's works we can see that this intellectual activity became so systematical and profound that we can speak of forming one sub discipline in Plato studies. According to the several characteristic starting points, there can be differentiated several paradigms in interpreting Plato's philosophy: Schleiermacher's romantic paradigm, developmental paradigm, Krämer s and Strauss ' esoteric paradigm, analytic and dramatic paradigm. With no intention to support one of these theories, this article tends to argue about the (iobjective " attempts to interpret Plato's works and to indicate that today's systematic interpreter should go back discovering the i(truth", more than discovering the “meaning" of Plato's philosophy.
Keywords: HISTORY OF PHILOSOPHY; INTERPRETATION; PARADIGM; PLATO; DIALOGUES